Process changes evaluation using segregated temperature versus enthalpy plot [electronic resource] - 491025 Hoo, Wei Kiong (2009)
Project Paper (Sarjana Muda Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2009